Contribution of polyol pathway to arteriolar dysfunction in hyperglycemia. Role of oxidative stress, reduced NO, and enhanced PGH(2)/TXA(2) mediation. - Toth, E; Racz, A; Toth, J; Kaminski, P; Wolin, MS; Bagi, Z; Koller, A (2007)
Hyperglycemia increases glucose metabolism via the polyol pathway, which results in elevations of intracellular sorbitol concentration. Thus we hypothesized that elevated level of sorbitol contributes to the development of hyperglycemia-induced dysfunction of microvessels. In isolated, pressurized (80 mmHg) rat gracilis muscle arterioles (approximately 150 microm), high glucose treatment (25 mM) induced reduction in flow-dependent dilation (from maximum of 39 +/- 2% to 15 +/- 1%), which was significantly mitigated by an aldose reductase inhibitor, zopolrestat (maximum 27 +/- 2%). Increasing doses of sorbitol (10(-10)-10(-4) M) elicited dose-dependent constrictions (maximum 22 +/- 3%), which were abolished by endothelium removal, a prostaglandin H(2)/thromboxane A(2) (PGH(2)/TXA(2)) receptor (TP) antagonist SQ-29548, or superoxide dismutase (SOD) plus catalase (CAT). Incubation of arterioles with sorbitol (10(-7) M) reduced flow-dependent dilations (from maximum of 39 +/- 2% to 20 +/- 1.5%), which was not further affected by inhibition of nitric oxide synthase by N(omega)-nitro-l-arginine methyl ester but was prevented by SOD plus CAT and mitigated by SQ-29548. Nitric oxide donor sodium nitroprusside-induced (10(-9)-10(-6) M) dilations were also decreased in a SQ-29548 and SOD plus CAT-reversible manner, whereas adenosine dilations were not affected by sorbitol exposure. Sorbitol significantly increased arterial superoxide production detected by lucigenin-enhanced chemiluminescence, which was inhibited by SOD plus CAT. Sorbitol treatment also increased arterial formation of 3-nitrotyrosine. We suggest that hyperglycemia by elevating intracellular sorbitol induces oxidative stress, which interferes with nitric oxide bioavailability and promotes PGH(2)/TXA(2) release, both of which affect regulation of vasomotor responses of arterioles. Thus increased activity of the polyol pathway may contribute to the development of microvascular dysfunction in diabetes mellitus.